A MYXOMATOSIS CASE IN GREECE - ΣΤΟΦΟΡΟΣ, Ε. Ν.; ΜΑΣΤΡΟΓΙΑΝΝΗ-ΚΟΡΚΟΛΟΠΟΥΛΟΥ, Μ.; ΡΑΝΤΣΙΟΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 1974)
During October 1973 myxomatosis on clinical grounds has been apeared the first in one big breeding of rabbits. These rabbits were imported from England and were not vaccinated against myxomatosis. The autors studied the disease from the clinical point of view as well as using Laboratory tests such as experimental inoculation, isolation of the virus on tissue culture and embryonated eggs and immunodiffusion. They used histological methods too. All the above investigations strongly suggest that the disease in cause was myxomatosis.